PENGGUNAAN STATISTIK DALAM PENELITIAN SOSIOLOGI - Partini * (Pendidikan Sosiologi FIS UNY, 2008)
The usage of statistic in social research, particularly in sociology is very uncomplicated and straightforward as long as the related researcher understands the basic argument from the chosen statistic formula. The choosing of specific formula is based on the type and data quality in order to get a more precise and accurate formula. The precision and accuracy in choosing the technique and statistic formula strongly define the quality of conducted research so that the formulizing of the summary is more precise, too. Statistic is nothing but a mean to create a more “meaningful” data. The usage itself is varies and the right understanding is not only based on the number resulted manually or computerize which usually used on the SPSS program but also have to be supported with the concept and theory. Furthermore, the understanding can also be get from research result conducted by other and from a balance battle of concept and empiric fact. Simply by using this method, the results can be accepted by others and can be more meaningful particularly for the sake of science development and policy makers. One of the excellences of by using the quantitative research method that usually applies the statistic formula can be used to predict. Moreover, the results and the summary can be generalized to the condition of population so that those can be utilized by a lot of people. Keywords: Statistic, Quantitative Method, Sociological Research